2023
DOI: 10.3389/fonc.2023.1099624
|View full text |Cite
|
Sign up to set email alerts
|

Gradual deterioration of fatty liver disease to liver cancer via inhibition of AMPK signaling pathways involved in energy-dependent disorders, cellular aging, and chronic inflammation

Abstract: IntroductionHepatocellular carcinoma (HCC) is the most prevalent primary liver cancer kind. According to recent research, a fatty liver increases the risk of hepatocellular cancer. Nevertheless, the AMPK signaling pathway is crucial. In addition, 5’-AMP-activated protein kinase (AMPK) is strongly linked to alterations in the tumor microenvironment, such as inflammation, hypoxia, and aging. The objective of this study is to evaluate the impact of the AMPK signaling pathway on the progression of fatty liver to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Our research has further revealed that Veillonellaceae , Alistipes , Enterobacteriales , and Firmicutes can promote the formation of ICC through the regulation of the AMPK signaling pathway and the mTOR signaling pathway. Meng et al (2023) have similarly reported that alterations in the AMPK- mTOR signaling pathway can exacerbate the progression of disrupted energy metabolism, chronic inflammation, hypoxia, and cellular aging within the tumor microenvironment. These factors collectively promote the transformation of fatty liver into liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our research has further revealed that Veillonellaceae , Alistipes , Enterobacteriales , and Firmicutes can promote the formation of ICC through the regulation of the AMPK signaling pathway and the mTOR signaling pathway. Meng et al (2023) have similarly reported that alterations in the AMPK- mTOR signaling pathway can exacerbate the progression of disrupted energy metabolism, chronic inflammation, hypoxia, and cellular aging within the tumor microenvironment. These factors collectively promote the transformation of fatty liver into liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of HCC, a recent study found that AMPK signaling pathway plays a crucial role in the transformation of fatty liver into HCC. Malignant changes in cell microenvironment inhibit AMPK signaling pathway and then cause a series of changes in cell processes, including metabolic disorders, cell senescence, and chronic inflammation of liver, which deepens the transformation of normal cells into cancer cells (Meng et al, 2023). An article published in Hepatology clearly indicates that metabolic differences between HCC cells and normal liver cells, especially in glutamine metabolism, contribute to the development of HCC tumors.…”
Section: The Ampk Signaling Pathway and Hccmentioning
confidence: 99%